Reintroducing a keystone burrowing rodent to restore an arid North American grassland: challenges and successes. Issue 5 (30th January 2018) - Davidson, Ana D.; Hunter, Elizabeth A.; Erz, Jon; Lightfoot, David C.; McCarthy, Aliya M.; Mueller, Jennifer K.; Shoemaker, Kevin T.
Abstract : Prairie dogs ( Cynomys spp.) are important ecosystem engineers in North America's central grasslands, and are a key prey base for numerous predators. Prairie dogs have declined dramatically across their former range, prompting reintroduction efforts to restore their populations and ecosystem functions, but the success of these reintroductions is rarely monitored rigorously. Here, we reintroduced 2, 400 Gunnison's prairie dogs ( C. gunnisoni ) over a period of 6 years to the Sevilleta National Wildlife Refuge, in central New Mexico, U.S.A., a semi‐arid grassland ecosystem at the southern edge of their range. We evaluated the population dynamics of prairie dogs following their reintroduction, and their consequent effects on grassland vertebrates. We found postrelease survival of prairie dogs stabilized at levels typical for the species (ca. 50%) after approximately 1 month, while average annual recruitment was ca. 0.35 juveniles per female, well below what was required for a self‐sustaining, stable population. Extreme drought conditions during much of the study period may have contributed to low recruitment. However, recruitment increased steadily over time, indicating that the reintroduced colony may simply need more time to establish in this arid system. We also found well‐known associates of prairie dog colonies, such as American badgers ( Taxidea taxus ) and burrowing owls ( Athene cunicularia ), were significantly more common on the colonies than off. After 7 years, we have yet to meet our goal of establishing a self‐sustaining population of Gunnison's prairie dogs in this semi‐arid grassland. But despite the uncertainty and challenges, our work shows that reestablishing keystone species can promote ecosystem restoration.